The Effects of Brand Image, Relationship Marketing, and Customer Satisfaction on Trust and the Decision to Enroll at Universitas 17 Agustus 1945 In Surabaya - Alif Kurniawan Wiratama; Siti Mujanah; Sumiati Sumiati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to examine and analyze the effects of Brand Image, Relationship Marketing, and Customer Satisfaction on Decision to Enroll, with Trust serving as a mediating variable among students of Universitas 17 Agustus 1945 Surabaya. The study employed a quantitative approach with a causal research design. The population consisted of students of Universitas 17 Agustus 1945 Surabaya, and 180 respondents were selected using a non-probability purposive sampling technique. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the assistance of SmartPLS software. The findings indicate that Brand Image, Relationship Marketing, and Customer Satisfaction have positive and significant effects on both Trust and Decision to Enroll. Furthermore, Trust has a positive and significant effect on Decision to Enroll and is proven to mediate the relationships between Brand Image, Relationship Marketing, and Customer Satisfaction and Decision to Enroll. These results suggest that a strong institutional image, effective relationship marketing practices, and high customer satisfaction are essential factors in building students’ trust and encouraging their enrollment decisions. Therefore, Universitas 17 Agustus 1945 Surabaya should continuously strengthen its brand image, enhance relationship marketing strategies, and improve customer satisfaction through high-quality academic and non-academic services to foster greater trust and increase prospective students’ intention to enroll.